FAKTOR FAKTOR PENYEBAB TINGGINYA KASUS PERCERAIAN PADA PASANGAN USIA MUDA (16-22 TAHUN) TERHADAP POLA ASUH ANAK DI KECAMATAN BUKIT KABUPATEN BENER MERIAH - Fiqih Dinanti Silalahi; Mawadhah Yusran; Hudnah; Nurlaely HS (Jurnal Ilmiah Cerebral Medika, 2026)
ABSTRACT Children is victim main from A divorce. Divorce between Mother and father will disturbing pattern foster children, if in a way term long Keep going increasing number divorce can lower quality man Indonesia. Research This done For know Factors causing the high number of divorce cases among young couples (16-22 years) regarding child rearing patterns in Bukit District, Bener Meriah Regency. Researcher This is study quantitative. Study This use design cross sectional. With amount overall population as many as 78 people (aged 16-22 years). So big sample used in study This as many as 78 respondents (total population ). Based on results test Chi-square show p value (0.014) <α (0.05) means There is influence factor economy with Pattern Foster Care child. Results calculation show p value (0.014) <α (0.05) means There is influence domestic violence factors with Pattern Foster Care child . result calculation show p value (0.759) >α (0.05) means No There is influence factor family with Pattern Foster Care child. Results calculation show p value (0.000) <α (0.05) means There is influence factor depression motherwith Pattern Foster Care child . Results calculation show p value (0.000) α (0.05) means There is influence baby blues factor with Pattern Foster Care child. From the results study can conclusion that There is connection economy family, domestic violence, depression time pregnancy and baby blues with pattern foster child. While proximity with family No There is connection with pattern foster child. For Respondent expected to be willing guard harmony in House stairs, so that formed harmonious family. Keywords : Economy, Domestic Violence, Depression, Baby Blues, Patterns Foster Care Child